A new Lean Six Sigma framework for improving competitiveness - Silva, Iris Bento da; Godinho Filho, Moacir; Agostinho, Oswaldo Luiz; Lima Junior, Orlando Fontes (Acta Scientiarum. Technology, 2019)
Manufacturing companies strive for ever-increasing competitiveness through productivity and quality. This goal can be achieved through the implementation of lean manufacturing and six sigma methodologies. Lean manufacturing adds value by reducing waste, while six sigma eliminates variability. In this context, this article proposes a new framework within Lean Six Sigma circumstances. The framework was proposed by means of an exhaustive literature review which identified the positive points of other Lean Six Sigma frameworks available on literature. The framework was applied to a case study, and the assessments were based on semi-structured questionnaires and analysis of records and documents. The implementation was carried out in a manufacturing company in Brazil, which belongs to an American-based multinational. In the case study described herein, the manufacturing company established the proposed framework to support the combination of lean manufacturing and six sigma and introduced an enterprise-wide culture of project through the proposed Lean Six Sigma framework, which resulted in significant benefits.